2018
DOI: 10.1016/j.chembiol.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

A Proposed Mechanism for Neurodegeneration in Movement Disorders Characterized by Metal Dyshomeostasis and Oxidative Stress

Abstract: Shared molecular pathologies between distinct neurodegenerative disorders offer unique opportunities to identify common mechanisms of neuron death, and apply lessons learned from one disease to another. Neurotoxic superoxide dismutase 1 (SOD1) proteinopathy in SOD1-associated familial amyotrophic lateral sclerosis (fALS) is recapitulated in idiopathic Parkinson disease (PD), suggesting that these two phenotypically distinct disorders share an etiological pathway, and tractable therapeutic target(s). Despite 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 92 publications
0
36
0
2
Order By: Relevance
“…Even if the real causing mechanisms of Parkinson's disease are still under investigation, it seems that oxidative stress plays a central role in the neurodegeneration associated with the disease, being able to cause most of the cellular impairments typical of Parkinson's disease that, in turn, can lead to the generation of even more ROS in a self‐reinforcing cycle . Similarly to what we previously mentioned about Alzheimer's disease, the low level of antioxidant enzymatic activity like superoxide dismutase (SOD) or glutathione peroxidase (GPx) observed in Parkinson's disease patients seems to confirm the link between oxidative stress and the disease . Currently, there are no treatments able to revert the neurodegeneration of the dopaminergic neurons, and the gold standard in Parkinson's disease treatment is still the use of 3,4‐dihydroxy‐ l ‐phenylalanine ( l ‐DOPA) .…”
Section: Neurological Diseases Associated To Oxidative Stressmentioning
confidence: 53%
See 2 more Smart Citations
“…Even if the real causing mechanisms of Parkinson's disease are still under investigation, it seems that oxidative stress plays a central role in the neurodegeneration associated with the disease, being able to cause most of the cellular impairments typical of Parkinson's disease that, in turn, can lead to the generation of even more ROS in a self‐reinforcing cycle . Similarly to what we previously mentioned about Alzheimer's disease, the low level of antioxidant enzymatic activity like superoxide dismutase (SOD) or glutathione peroxidase (GPx) observed in Parkinson's disease patients seems to confirm the link between oxidative stress and the disease . Currently, there are no treatments able to revert the neurodegeneration of the dopaminergic neurons, and the gold standard in Parkinson's disease treatment is still the use of 3,4‐dihydroxy‐ l ‐phenylalanine ( l ‐DOPA) .…”
Section: Neurological Diseases Associated To Oxidative Stressmentioning
confidence: 53%
“…Similarly to what we described concerning Alzheimer's disease, it is not clear whether oxidative stress is a cause of Parkinson's disease or rather a consequence of other cellular impairments. For example, we discussed the role of mitochondrial dysfunction in Parkinson's disease pathogenesis, but mithocondria are not only producer of ROS, yet also one of the main targets of oxidative stress‐induced damage . It has been demonstrated that α‐synuclein aggregation is affected by elevated ROS levels .…”
Section: Neurological Diseases Associated To Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…These two regions (dimer interface -loop IV and the electrostatic loop -loop VII) are frequently affected by genetic and non-genetic factors, the later including an array of posttranslational modifications (PTM, e.g. acylation, sumoylation, ubiquitination, glycation) 67,68 . Dimer interface modifications have been shown to enhance monomer formation 69 , increasing the production of high molecular weight inclusions 70 .…”
Section: Discussionmentioning
confidence: 99%
“…As an example, many neurotransmitters have been implicated in MS. Glutamate excitotoxicity has been implicated in MS. 214,215 Research indicates that MtD plays an important role in glutamate-induced neuronal excitotoxicity, 216 by impacting upon the ability of the neuron to resist excitotoxic stress. 217,218 Glutamate excitotoxicity induces OS 219 and glutamate excitotoxicity is in part driven by the failure of antioxidant mechanisms to preserve cellular redox homeostasis. 220 OS modulates the uptake of GABA and glutamate 221 and plays a role in glutamate excitotoxicity.…”
Section: Other Factorsmentioning
confidence: 99%